2010
DOI: 10.1016/j.ejphar.2010.08.022
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of the anti-hyperalgesic effect of ketamine and of its isomers by the administration of ifenprodil

Abstract: Intrathecal or epidural administration of NMDA (N-methyl-D-aspartate) receptors antagonists, in special ketamine and ifenprodil are used to control moderate to severe hyperalgesia in humans. Activation of NMDA receptor usually requires binding of two agonists, glutamate and glycine, in different receptor subunits. Ketamine is a NMDA receptor antagonist and acts at phencyclidine site in NR1 subunit while ifenprodil is a selective NR2B subunit antagonist of NMDA receptor. The aim of this study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The current study demonstrated that ethanol may synergistically potentiate ketamine inhibition of NMDA-induced responses, suggesting that the binding site of ethanol may be different to that of ketamine in NMDA receptors and both binding sites may interact with each other in regulating NMDA receptor function. Actually, a recent study also showed that ifenprodil, a selective NMDA receptor GluN2B subunit antagonist, may enhance the anti-hyperalgesic effect of ketamine [26]. …”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated that ethanol may synergistically potentiate ketamine inhibition of NMDA-induced responses, suggesting that the binding site of ethanol may be different to that of ketamine in NMDA receptors and both binding sites may interact with each other in regulating NMDA receptor function. Actually, a recent study also showed that ifenprodil, a selective NMDA receptor GluN2B subunit antagonist, may enhance the anti-hyperalgesic effect of ketamine [26]. …”
Section: Discussionmentioning
confidence: 99%